European Union and protagonists of archival protection - Melik, Jelka (Atlanti +, 2025)
Purpose: The purpose of our paper is to show that historical archives in Slove-nia and in other states, members of European Union, need changes in order to play a more important role in the society. Method/approach: The method used in our paper is first of all a descriptive method, showing the state of archives in Europe today. By using the comparative method, we compared the situation in the archival field in the European Un-ion with the vision of the future development of the European Union. The third method applied is the method of analysis and synthesis. Finally, the compilation method was used to summarize the findings. Results: We found that changes in the arhival field are necessary both in the Member States and at the level of the European Union.Conclusion/findings: In conclusion, we have identified the need for a threefold transformation of the archival field. First, it must be emancipated from its tradi-tional confinement within the cultural sector, with greater emphasis placed on the primary mission of archives: their essential contribution to democracy and the rule of law. Second, the relationship between public archives and records crea-tors must evolve. The archival profession should become more forward-looking, integrating the roles of both historical archivist and records manager. The ar-chivist must emerge as a key actor in the protection of archives, with responsi-bilities spanning from the creation of documents to their long-term preservation in historical repositories.Finally, transformation is also needed at the European Union level. The EU should take a more active role in identifying and supporting the archival needs of its Member States. Archival policy and preservation must become a shared concern and responsibility of the European Union.
Keywords: archives; archivist; arhivar; Arhivi; historical archives; records manager; upravitelj dokumentov; zgodovinski arhivi